If b was 3 a will be 6 because 2*3=6
and for the second part b will be 3.5 because 2*3.5=7
Answer:
Step-by-step explanation:
-3i √(-40) = -3i √40i² ...(i² = - 1)
= -3i √40 i
-3i √(-40) = 3√40
Step-by-step explanation:
x+100°=180°{being straight angle}
x=180-100
x=80°
again,
45°+x+y=180°{sum of angle of triangle}
45+80+y=180
y=180-125°
y=55°
hope it helps.
Answer:
8x^8/3 y^4 - The first option
Step-by-step explanation:
The first thing we need to do is the exponent outside the bracket and leave the 8 till last, because exponents always come before multiplying coefficients. When an term with an exponent is multiplied by another exponent outside a bracket, the exponents of both terms are multiplied by the exponent outside the bracket.
This means that the expression is now:
8(x^2*4/3 y^3*4/3)
First we can so the x term. The x term already has an exponent of 2, so the 2 is multiplied by the 4/3 exponent outside the bracket. 2*4/3 = 8/3, so the x term is now: x^8/3
The same happens to the y term: 3*4/3 simplifies to 4, so the y term is now y^4.
So now our expression is:
8(x^8/3 y^4)
Now the 8 outside the bracket simply multiplies on to the whole term so we finish with:
8x^8/3 y^4 - The first option.
Hope this helped!